Does Slang Threaten the Structure of the Mother Tongue? An Analysis of Generative Grammar in Indonesian Adolescent Language - Rachelia Putri, Vanya (International Journal of Language and Ubiquitous Learning, 2025)
Background. Language is a dynamic and adaptive system that evolves in response to its users’ needs. Among Indonesian adolescents, the rise of slang has raised public concern regarding its potential to disrupt the structural integrity of the Indonesian mother tongue. This concern stems from fears that informal variations may erode grammatical norms and weaken formal language proficiency. Purpose. This study aims to determine whether the use of slang among teenagers represents a threat to the syntactic norms of formal Indonesian or constitutes a natural form of linguistic variation that aligns with social and cognitive development. Method. A qualitative descriptive method was employed, focusing on data collected from popular social media platforms such as TikTok, Instagram, and Twitter. Purposive sampling was used to identify common slang expressions. The data were then analyzed using the frameworks of generative grammar and psycholinguistics to explore structural changes and their cognitive implications. Results. Analysis of three representative slang-based sentences revealed that while slang tends to omit formal elements and compress sentence structures, essential syntactic patterns—especially the subject-verb-object (SVO) sequence—remain intact. From a psycholinguistic perspective, adolescents show cognitive flexibility in both producing and interpreting these expressions contextually, rather than relying strictly on formal rules. Conclusion. The study concludes that adolescent slang does not undermine linguistic competence. Instead, it enriches expressive ability and serves as a marker of social identity. Slang is best understood as an adaptive form of linguistic creativity shaped by digital culture and generational shifts, rather than a degradation of language.